PERINEAL LACERATIONS DURING SPONTANEOUS VAGINAL DELIVERY (Frontier in Medical and Health Research, 2025)
Introduction A common postpartum complication is perineal tears. Affected women may experience ongoing physical discomfort psychological stress and social limitations despite the fact that it is frequently dismissed as a minor problem. Pain in the perineum can limit daily activities and hinder mobility. Local information on the prevalence of perineal lacerations during spontaneous vaginal delivery is scarce. In order to improve preventive measures and raise the standard of care for impacted women this study was carried out to assess the frequency of perineal lacerations.Objective to ascertain the prevalence of perineal lacerations among nulliparous women who visit a tertiary care facility during spontaneous vaginal delivery. Setting The study was conducted between January 28 and July 28. Department of Obstetrics and Gynecology, Civil Hospital Karachi. Design The studys descriptive cross-sectional methodology involved the recruitment of 139 nulliparous women who had singleton pregnancies. Every patient was evaluated for perineal cuts. A proforma created specifically for this purpose was used to gather all the data.Results The average age of the female participants was 30. 50±4. 50 years. Among nulliparous women the frequency of perineal lacerations during spontaneous vaginal birth was 38. 85 percent (54/139). Conclusion Perineal cuts during spontaneous vaginal delivery were common among nulliparous women in the current study. Significant post-natal morbidity is caused by perineal tears. To reduce the risk of perineal trauma and morbidity it is advised to identify risk factors have senior doctors closely monitor and supervise difficult or instrumental deliveries and provide adequate perineal support.